Respuesta :

Sum of 3 angles = 180
50 + 27 + unknown  = 180
unknown  = 180 - 50 - 27 = 103 derees 

The answer is: 53° .
_____________________________________
Explanation: 
___________________________________
All three angles in ANY triangle add up to: 180° .
__________________________________________
We are given the measurements of two of the angles in a triangle,
     50, and 27.  We know that the sum of the three (3) angles = 180.

We want the measurement  ofthe unknown angle, which we will represent with the variable, "x".
_________________
Method 1:
___________________________________________
So, 50 + 27 + x = 180 ;
__________________________
→ Subtract "50" and subtract "27" from EACH SIDE of the equation; 
         to isolate "x" on one side of our equation; and to solve for "x" ;
_________________________________________________
→ 50 + 27 + x − 50 − 27 = 180 − 50 − 27 ;  
_____________________________
    → to get:  x = 53° .
________________________________________
Method 2:
___________________________
So, 50 + 27 + x = 180 ;
___________________________
 → Add:  "50 + 27" ; to get, "77" ; 
___________________________
→ Rewrite as: 77 + x = 180 ; 
_________________________
→ Now, subtract "77" from EACH SIDE of the equation; 
         to isolate "x" on one side of our equation; and to solve for "x" ;
______________________________________________________
→   77 + x − 77 = 180 − 77 ;
_____________________________
→  to get:  x = 53° .
_________________________________
Method 3:
___________________________________
 → 180 − (50 + 27) = x ;  Solve for "x"
________________________________
       → 50 + 27 = 77 ;
________________________________________   
→ Rewrite the equation, substituting "77" in lieu of "(50 + 27)" ;
 _________________________________________
  → 180 − 77 = x ;  → 53 = x ;  ↔ x = 53° .
__________________________________________
Method 4:
________________________
180 − (50 + 77) = x ; solve for 'x"; 
___________________________
→ Note the "distributive property of multiplication:
____________________________________
      a*(b + c) = ab + ac ; AND:
  
      a*(b − c) = ab − ac ;
_____________________________________
→ So, we have:  180 − (50 + 77) = x ;
_____________________________________
Treat this as: " 180 − 1(50 + 77)" ;
_______________________________________
→ Note, the coefficient "1" is implied; and makes since, since any value, multiplied by "1" equals that same value.

→ We treat this number as "-1", since there is a subtraction sign; so, let us consider the expression:  " -1(50 + 77) " 
_______________________________________
    →   -1(50 + 77)  = (-1*50) + (-1*77) ;

    →  -50 + (-77) = -50 -77 = -127 ;
__________________________________________________
      →So rewrite the equation: Bring down the "180";
                                      & bring down the "-127" and the: "= x " ; 
___________________________________________________
           → 180 − 127 = x ;  to get: →  53 = x ;   ↔   x = 53° . 
___________________________________________________

ACCESS MORE